DRIVER RESPOND TO PRE-COLLISION SCENARIO AT INTERSECTION IN AUTONOMOUS VEHICLE - Mokhtar, N.H.; Takada, H.; Matsuura, Y. (Journal of Advanced Manufacturing Technology (JAMT), 2019)
Research on automation system development is attracting a lot of attention from researchers, automotive industry manufacturers and leading technology brands. This study focus is on SAE level 3, the vehicle steering, accelerator pedal and brake pedal are controlled autonomously. The decrement in controlling vehicle and driving task has the possibility to reduce the road crash resulted in an essential change in driver role from active to passive. The effect of role change leads to decrement of situation awareness and reduce driver abilities to control manual vehicle at the right time and manner. Therefore, research on recognition times in complex and actual situations are critical. The primary purpose was to analyze the driver’s ability to recognize pedestrian, bicycle and vehicle pre-collision at intersection in the automated vehicle. The road conditions were complicated and imitated a real driving scenario. The statistical tools used for analysis were the F-test, t-test and ANOVA method. This finding shows that the subject can instantaneously recognize unintended acceleration at a low velocity and relative velocity in a pre-collision scenario with pedestrian. The implication of these results is in developing an automated vehicle system related to driver recognition. These findings provide insights that can be useful in developing autonomous vehicles.